2008
DOI: 10.1175/2008jtecha1008.1
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Reflectivity in a Networked Radar Environment

Abstract: A system for reflectivity and attenuation retrieval for rain medium in a networked radar environment is described. Electromagnetic waves backscattered from a common volume in networked radar systems are attenuated differently along the different paths. A solution for the specific attenuation distribution is proposed by solving the integral equation for reflectivity and attenuation. The set of governing integral equations describing the backscatter and propagation of common resolution volume are solved simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 11 publications
0
27
0
7
Order By: Relevance
“…For further improvement, the next step will be the implementation of attenuation correction algorithms that use the advantage of a network (e.g. Chandrasekar and Lim, 2008;Srivastava and Tian, 1996;Testud and Amayenc, 1989). Better estimation of attenuation can lead to better precipitation estimates, because the relation between attenuation and precipitation is more stable than the relation between reflectivity and precipitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For further improvement, the next step will be the implementation of attenuation correction algorithms that use the advantage of a network (e.g. Chandrasekar and Lim, 2008;Srivastava and Tian, 1996;Testud and Amayenc, 1989). Better estimation of attenuation can lead to better precipitation estimates, because the relation between attenuation and precipitation is more stable than the relation between reflectivity and precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…These methods allow for estimation of attenuation and correction of observed reflectivities simultaneously, if at least two radars observe a common volume (Testud and Amayenc, 1989;Kabeche and Testud, 1995;Srivastava and Tian, 1996;Tian and Srivastava, 1997;Chandrasekar and Lim, 2008;Lim et al, 2011). In the last few years, several networks consisting of different types of X-band radars have been installed to fill gaps in nationwide networks of C-or S-band radars, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Attenuation is a known issue for precipitation estimation using X-band radars (Seo et al 2010;Berne and Krajewski 2013). The CASA system uses the network reflectivity retrieval technique (Chandrasekar and Lim 2008) and the network based attenuation correction technique (Lim et al 2011) to mitigate the effects of attenuation. Lim et al (2011) showed that the technique works robustly in real time in retrieving attenuation corrected reflectivity.…”
Section: Figure 1 the Hl-rdhm Domain Encompassing Fortmentioning
confidence: 99%
“…Due to the reduced cost of S-or C-band weather radars attention was moved from X-band to these systems during the 1970s and 1980s. However, with the launch of the TRMM satellite (Simpson et al, 1988) in 1997 and the CASA project, where a complementary X-band radar network is being proposed (Chandrasekar and Lim, 2008), better attenuation correction schemes have become of major interest and new research into X-band radar has begun. Where Hitschfeld and Bordan (1954) proposed a simple forward scheme to correct for attenuation, more sophisticated backward methods, which use a Path Integrated Attenuation constraint, have been developed since (e.g., Marzoug and Amayenc, 1994;Delrieu et al, 1997).…”
Section: Z Van De Beek Et Al: High-resolution X-band Radar For Rmentioning
confidence: 99%